(untitled) (REMUNOM, 2025)
The teaching of redox reactions and electrochemistry in higher education still faces challenges due to conceptual complexity and the predominance of memorization-based methods. As an alternative, this study presents the development and application of UNO REDOX, an educational card game adapted from the classic UNO, designed for the Pharmaceutical Analysis course at UFPA. The game allows students to practically build electrochemical cells, linking theory and practice in an engaging and interactive way. The activity was evaluated by 30 participants, who highlighted aspects such as visual appeal, rule clarity, and pedagogical relevance. The results indicate that UNO REDOX enhanced engagement, motivation, and understanding of the concepts, proving to be an innovative and accessible tool for Chemistry teaching.